2
$\begingroup$

Hello I have to solve $\gcd (n^3+3n^2-5 , n+2)$ with bezout

Here’s how I did it:

bezout says $a$ and $b$ are co prime if and only if $au+bv = 1$.

Then I did : $(n+2)(n^2+n-2) -(n^3+3n^2-5)$

I found one so their $\gcd$ is equal to $1$.

Did I get the right method ?

Sorry for my bad english !!!

$\endgroup$
7
  • 2
    $\begingroup$ It seems you did well. $\endgroup$
    – Qurultay
    Commented May 17, 2021 at 15:03
  • $\begingroup$ Okay thanks for your comment it helps me a lot $\endgroup$
    – achla95
    Commented May 17, 2021 at 15:03
  • 1
    $\begingroup$ You don't need Bezout, Euclid is enough. $\endgroup$
    – user65203
    Commented May 17, 2021 at 15:17
  • $\begingroup$ But @YvesDaoust bezout work ? $\endgroup$
    – achla95
    Commented May 17, 2021 at 15:19
  • 1
    $\begingroup$ $(n+2)(n^2+n-2) -(n^3+3n^2-5)=1$ is what the extended Euclidean algorithm gives in $\mathbb Q[n]$ as a polynomial ring: WA $\endgroup$
    – lhf
    Commented May 17, 2021 at 20:18

1 Answer 1

1
$\begingroup$

$$A(n^3+3n^2-5) + B(n+2) = 1$$

This isn't a blueprint for a general method of finding a solution. I am going to take advantage of the fact that the second polynomial is $n+2$, a first degree polynomial.

Let $m = n+2$. Then

$$n^3+3n^2-5 = (m-2)^3+3(m-2)^2-5 = m^3 - 3m^2 -1$$

So we need to solve

$$A(m^3 - 3m^2 -1) + B(m) = 1$$

If we let $A=-1$, we get

\begin{align} A(m^3 - 3m^2 -1) + B(m) &= 1 \\ -1(m^3 - 3m^2 -1) + B(m) &= 1 \\ Bm &= m^3 -3m^2 \\ B &= m^2 - 3m \\ B &= (n+2)^2-3(n+2) \\ B &= n^2 + n - 2 \end{align}

It is easy to check that

$$A(n^2 + n - 2) + B(n+2) = (-1)(n^3+3n^2-5) + (n^2 + n - 2)(n+2) = 1 $$

$\endgroup$
1
  • $\begingroup$ Thank you for your explanations this helped me a lot despite having taken time to understand. $\endgroup$
    – achla95
    Commented May 18, 2021 at 14:43

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .